RESPON MASYARAKAT TERHADAP SUPELTAS (SUKARELAWAN PENGATUR LALU LINTAS) DI KOTA PEKANBARU - Dhastia Sari; Syafrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
affic jam is one of the problems that occur in big city, it is caused by the number of vehicles that keep increasing every year. Pekanbaru is one of the cities that face this problem. Some people take advantage of this problem to earn a living as supeltas (volunteer traffic control) or Pak Ogah. The formulations of the problem that being discussed in this research are as follows: (1) how is the response of the society towards supeltas clearing congestion in Pekanbaru and; (2) what are the expectations of the society towards traffic police, supeltas, and government. Research purposes to analyze response of the society towards supeltas and to know expectations of society towards traffic police, and goverment. This research uses a theory from Sukamto which discuss on this phenomenon in three factors; cognitive, affective, conative. The data was analyzed using descriptive design and quantitative approach. The data collecting technique is accidental sampling, it means that everyone who accidently meets the researcher can be the respondent, and the respondents in this research are 100 people. The result from this research can be concluded that for the cognitive factor the response of society toward supeltas in Pekanbaru is already good, while the affective factor shows that the society not fully agree with the existence of supeltas , and the result for the conative factor is mediocre. On the other hand, people expect traffic police to responsibly do their duty, for the supeltas to do their job voluntarily, and als the government should pay attention to the traffic facility.  Keywords : Traffic Jam, Publics Respones, Supeltas (Pak Ogah)